A new PK equivalence test for a bridging study. Issue 5 (2nd September 2016) - Novick, Steven J.; Zhang, Xiang; Yang, Harry
ABSTRACT: In a bridging study, the plasma drug concentration–time curve is generally used to assess bioequivalence between the two formulations. Selected pharmacokinetic (PK) parameters including the area under the concentration–time curve, the maximum plasma concentration or peak exposure (Cmax ), and drug half-life (T1/2 ) are compared to ensure comparable bioavailability of the two formulations. Comparability in these PK parameters, however, does not necessarily imply equivalence of the entire concentration–time profile. In this article, we propose an alternative metric of equivalence based on the maximum difference between PK profiles of the two formulations. A test procedure based on Bayesian analysis and accounting for uncertainties in model parameters is developed. Through both theoretical derivation and empirical simulation, it is shown that the new method provides better control over consumer's risk.